High-barrier composite packaging material and preparation method thereof
By adopting a multi-layer structure with high barrier composite packaging material and using modified PVA and polylactic acid film-forming substances, the shortcomings of existing pharmaceutical packaging materials in the iodine-resisting scenarios are solved, and efficient drug protection and iodine preservation are achieved.
Patent Information
- Application Number
- CN202411868296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing pharmaceutical packaging materials perform poorly in iodine-resistant scenarios, with large iodine losses and the aluminum foil layer easily damaged, making it impossible to effectively protect the drugs.
A high-barrier composite packaging material consisting of an aluminum foil layer, a vinyl resin heat sealing coating, a composite coating, a VC glue coating, a polyurethane heat sealing coating and a polyvinyl chloride sheet are used. PVA and polylactic acid are used as the main film-forming substances in the composite coating, and compatibility and barrier properties are improved through the modification of functional particles.
It has achieved high resistance iodine function, good mechanical properties and comprehensive performance, effectively protects drugs and reduces iodine losses.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iodine barrier material preparation, and specifically relates to a high-barrier composite packaging material and a preparation method thereof. Background Art
[0002] Blister packaging, also known as blister packaging, referred to as PTP (Press through Packaging), is one of the main forms of pharmaceutical packaging and is suitable for mechanized packaging of solid dosage forms such as tablets, capsules, suppositories, and pills. However, for drugs currently packaged on the market, which contain a certain amount of iodine, ordinary PTP aluminum foil is used for packaging. Not only does the amount of iodine loss far exceed the requirement, but the aluminum foil layer is easily damaged by iodine, and the protective effect of the packaging cannot be achieved at all, and the use requirements in iodine-blocking scenarios cannot be met. Therefore, it is of great significance to develop barrier packaging materials with high iodine-blocking function.
[0003] In the prior art, an iodine-barrier aluminum foil blister packaging structure is disclosed in the applicant's earlier patent achievement CN220841724U, which discloses the specific composition of the packaging structure, but does not provide a detailed description of the materials used in each layer, especially the barrier layer; Patent document CN117183483A provides an iodine-barrier packaging material, including a cover film and a base film, the cover film includes a paper layer, a first aluminum foil layer and a first PET layer stacked in sequence from top to bottom, the base film includes a glue layer, a second PET layer, a second aluminum foil layer, and a polyamide layer arranged in sequence from top to bottom, in the preparation process of the polyamide layer, graphite carbon nitride and other materials are used, the cost is relatively high, and the performance of the obtained packaging material except iodine barrier needs to be further improved in other aspects.
[0004] After further searching relevant literature, the applicant found that there were not many research reports on iodine barrier packaging materials, and most of the research was on water barrier and gas barrier. However, giving packaging materials iodine barrier function is a practical problem faced by the packaging industry. Therefore, the present invention is proposed. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-barrier composite packaging material and a preparation method thereof, which has good iodine barrier function, good mechanical properties and excellent comprehensive performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high barrier composite packaging material, which is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin is added to deionized water, and then the first part of functional particles is added after stirring. After heating and stirring, solution I is obtained and set aside; (2) adding polylactic acid to the mixed solution, stirring, and then adding the second part of functional particles, heating and stirring, to obtain solution II; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0007] Preferably, in step (1), the mass ratio of PVA resin, deionized water, and the first part of functional particles is 60-80:10-15:4-8; the stirring treatment temperature is 50-65°C, and the treatment time is 2-6h; In step (2), the mass ratio of polylactic acid, mixed solution and the second part of functional particles is 20-40:6-12:4-8; the mass ratio of the first part of functional particles and the second part of functional particles is 1:1; the mixed solution is obtained by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4; the stirring treatment temperature is 50-65°C, and the treatment time is 2-6h.
[0008] Preferably, the preparation of functional particles comprises the following steps: S1. Modification of titanium dioxide: treating titanium dioxide in concentrated acid, filtering, washing and drying to obtain modified titanium dioxide; S2. Immobilization of titanium dioxide: chitosan is added to deionized water, and then the modified titanium dioxide obtained in step S1 is added, and after being stirred evenly, acetic acid is added to adjust the pH value of the system, followed by heating and stirring. After the treatment is completed, the modified chitosan is obtained by centrifugation, washing, and drying. S3, pre-modification of montmorillonite: adding montmorillonite to deionized water, adding CTAB under heating and stirring conditions, then maintaining the heating and stirring temperature for reaction, after the reaction is completed, filtering and drying to obtain pre-modified montmorillonite; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution after stirring, adding Tris-HCl buffer to adjust the pH value after stirring again, heating for reaction, centrifuging, washing and drying to obtain modified montmorillonite; S5. Compounding: adding the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 into deionized water respectively, heating and stirring, and then filtering, drying and sieving to obtain functional particles.
[0009] Preferably, in step S1, the concentrated acid is 98% concentrated sulfuric acid, the treatment temperature is 70-85° C., and the treatment time is 1-4 h; the dosage ratio of titanium dioxide to concentrated acid is 1 g: 3-6 mL.
[0010] Preferably, in step S2, the pH value of the system is 4.5-6.5; the dosage ratio of chitosan, deionized water, and modified titanium dioxide is 1 g: 5-10 mL: 0.45-0.65; The heating and stirring treatment temperature is 30~35℃, and the treatment time is 2~6h.
[0011] Preferably, in step S3, the usage ratio of montmorillonite, deionized water and CTAB is 1 g: 5-12 mL: 0.4-0.65 g; The heating and stirring temperature is 70~85℃, and the reaction time is 2~6h.
[0012] Preferably, in step S4, the pH value of the system is adjusted to 8-9; the dosage ratio of the pre-modified montmorillonite, deionized water, and dopamine aqueous solution is 1 g: 30-60 mL: 0.8-1.2 g; The concentration of dopamine aqueous solution is 0.45~0.85 g / mL; The heating reaction temperature is 35~45℃ and the reaction time is 6~18h.
[0013] Preferably, in step S5, the usage ratio of modified chitosan, modified montmorillonite and deionized water is 2 g: 0.5-0.8 g: 6-12 mL; The heating and stirring temperature is 30~35℃, and the heating and stirring treatment time is 2~6h; The sieving mesh number is 80~150 mesh.
[0014] In a second aspect, the present invention also provides a method for preparing the above-mentioned high barrier composite packaging material, comprising the following steps: (1) coating a vinyl resin heat-sealing adhesive on the surface of the aluminum foil layer and drying the adhesive to form a vinyl resin heat-sealing coating; (2) applying a coating liquid on the surface of the vinyl resin heat seal coating and drying it to form a composite coating; (3) Apply VC glue on the surface of the composite coating and form a VC glue coating after drying; (4) applying polyurethane heat-sealing adhesive on the surface of the VC glue coating, and drying to form a polyurethane heat-sealing coating to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
[0015] Preferably, the coating amount of the vinyl resin heat sealant is 5 to 8 g / m 2 ; The coating amount of the coating liquid is 3~5 g / m 2 ; The coating amount of VC glue is 4~6 g / m 2 ; The coating amount of polyurethane heat sealant is 5~8 g / m 2 .
[0016] Compared with the prior art, the present invention has the following beneficial effects: The iodine-barrier packaging material provided by the present invention is composed of a multi-layer structure, has good iodine-barrier function, good mechanical properties, and excellent comprehensive performance.
[0017] In the iodine-barrier packaging material provided by the present invention, the composite coating plays a key iodine-barrier effect. Specifically, the coating liquid used in the composite coating uses PVA and polylactic acid as main film-forming substances. The main reason is that a single PVA resin as a film-forming substance has insufficient moldability and poor flexibility, heat sealing and mechanical strength. Therefore, polylactic acid with good oxygen barrier and heat sealing properties is introduced. However, there is a compatibility problem when the two are directly mixed. Therefore, functional particles are introduced in the present invention to modify the two separately. The functional particles are compounded of organic and inorganic substances. Through specific treatment, their own dispersibility is guaranteed. Based on the rich functional groups introduced, the effect of "lubrication" between PVA and polylactic acid is played, thereby improving the compatibility of PVA and polylactic acid, thereby greatly improving the barrier performance of the composite coating.
[0018] In the present invention, the functional particles are mainly composed of titanium dioxide, montmorillonite, and chitosan. Titanium dioxide is introduced into PVA and polylactic acid as an inorganic filler. While improving the wear resistance of the coating, it can also effectively improve the density of the coating matrix and reduce the permeability of gas and water vapor. In order to improve its dispersibility and compatibility, the present invention performs a simple acid treatment on it to introduce groups (such as hydroxyl groups) to facilitate the improvement of its and chitosan's immobilization effect; the introduction of chitosan plays a very important role in the present invention. It has very rich groups and compatibility. As a medium material, on the one hand, it can form a composite system with PVA resin and polylactic acid, and on the other hand, it can form a compound with modified montmorillonite to improve the dispersibility of montmorillonite; and montmorillonite, as another inorganic filler used, can The mechanical properties, thermal stability and barrier properties of the coating are further improved by working together with titanium dioxide. In the specific use process, CTAB intercalation modification is first performed on it to initially improve the compatibility of montmorillonite, and the twisted migration channel formed by the increase in the interlayer spacing initially improves its barrier properties. In order to further improve its compatibility, dopamine is then introduced into the montmorillonite for modification in the present invention. The amino groups, hydroxyl groups and other groups contained in dopamine itself not only improve the composite properties of the modified montmorillonite and chitosan, but also form a hydrogen bond system between the amino groups and hydroxyl groups possessed by the functional particles and the PVA resin and polylactic acid, thereby improving the compatibility between the PVA resin and polylactic acid and between the PVA resin, polylactic acid and the functional particles, thereby ensuring the barrier properties and mechanical properties of the coating.
[0019] The preparation method of the iodine-blocking packaging material provided by the present invention mainly uses a four-layer coating process, is simple, and is easy to implement. DETAILED DESCRIPTION
[0020] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0021] In the present invention, titanium dioxide was purchased from Guangzhou Leisheng Technology Co., Ltd.; montmorillonite was purchased from Guangzhou Yifeng Chemical Technology Co., Ltd.
[0022] In the present invention, VC glue was purchased from Xi'an Tianyi Adhesive Materials Co., Ltd.; vinyl resin heat sealant was purchased from Shanghai Weike Optoelectronic New Materials Co., Ltd. with a brand name of VC-1100; PVA resin was purchased from Jining Fangyu Chemical Co., Ltd. with a brand name of 1799; polyurethane heat sealant was purchased from Michelman (Shanghai) Chemical Trading Co., Ltd.; polylactic acid was purchased from Nature Works, USA, with a model number of 3001D; and chitosan was purchased from Qingdao Yunzhou Biotechnology Co., Ltd.
[0023] In the present invention, the remaining matters not described are all conventional means known to those skilled in the art (such as coating method, drying and compounding, etc.); materials without source description are all commercially available.
[0024] It should be noted that the structure of each layer in the present invention can be adjusted according to actual needs, such as the thickness can be selected as follows: the thickness of the aluminum foil layer is 0.032 mm, the thickness of the polyvinyl chloride sheet is 0.03 mm; the thickness of the vinyl resin heat-sealing coating, the composite coating, the VC glue coating, and the polyurethane heat-sealing coating are all 0.015 mm.
[0025] In the present invention, the concentration of concentrated sulfuric acid is 98%.
[0026] The coating speed and drying temperature of vinyl resin heat sealant, coating liquid, VC glue and polyurethane heat sealant can be selected according to the actual characteristics of the product. For example, the coating speed of VC glue can be 50m / min, the drying temperature is about 160~175℃, and the composite pressure of semi-finished product and polyvinyl chloride sheet is 2.5kg / cm 2 The selection of the above process parameters can be actually selected by those skilled in the art as needed. The above parameters of the present invention are only examples and do not constitute a limitation on the protection scope of the present invention. The specific implementation is subject to what can be achieved by those skilled in the art.
[0027] Example 1
[0028] A high barrier composite packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin was added to deionized water in a mass ratio of 65:13:6, and then functional particles were added after stirring (the amount added was half of the mass of all functional particles). After heating and stirring (55°C, 3h), solution I was obtained and set aside. (2) According to the mass ratio of polylactic acid, mixed solution and functional particles being 35:9:6, polylactic acid was added to the mixed solution (prepared by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4), and then the functional particles were added after stirring (the amount added was half of the mass of all functional particles), and after heating and stirring (55°C, 3h), solution II was obtained; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0029] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (70°C, 1h) at a ratio of 1g titanium dioxide to concentrated acid (5.5mL). After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2. Immobilization of titanium dioxide: chitosan was added to deionized water, and then the modified titanium dioxide obtained in step S1 was added, and after being stirred evenly, acetic acid was added to adjust the pH value of the system to 5.5, followed by heating and stirring treatment (35°C, 3.5h). After the treatment was completed, the modified chitosan was obtained by centrifugation, washing, and drying. The amount ratio of chitosan, deionized water, and modified titanium dioxide was 1g: 10mL: 0.5; S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution (0.55 g / mL) after stirring, adding Tris-HCl buffer to adjust the pH value to 8.8 after stirring again, heating for reaction (40°C, 10 h), centrifuging, washing and drying to obtain modified montmorillonite; wherein the amount ratio of pre-modified montmorillonite, deionized water and dopamine aqueous solution is 1 g:45 mL:0.95 g; S5. Compounding: According to the usage ratio of modified chitosan, modified montmorillonite and deionized water being 2 g:0.65 g:10 mL, the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 are added into deionized water respectively, heated and stirred (35°C, 3.5 h), and then filtered, dried and sieved through 100 mesh to obtain functional particles.
[0030] In this embodiment, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0031] Example 2
[0032] A high barrier composite packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin was added to deionized water in a mass ratio of 65:12:6, and then functional particles were added after stirring (the amount added was half of the mass of all functional particles). After heating and stirring (55°C, 3h), solution I was obtained and set aside. (2) According to the mass ratio of polylactic acid, mixed solution and functional particles being 35:10:6, polylactic acid was added to the mixed solution (prepared by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4), and then the functional particles were added after stirring (the amount added was half of the mass of all functional particles), and after heating and stirring (55°C, 3.5h), solution II was obtained; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0033] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (75°C, 0.5h) at a ratio of 1g titanium dioxide to concentrated acid: 6mL. After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2. Immobilization of titanium dioxide: chitosan was added to deionized water, and then the modified titanium dioxide obtained in step S1 was added, and after being stirred evenly, acetic acid was added to adjust the pH value of the system to 5.5, followed by heating and stirring treatment (35°C, 4h). After the treatment was completed, the modified chitosan was obtained by centrifugation, washing, and drying. The amount ratio of chitosan, deionized water, and modified titanium dioxide was 1g: 10mL: 0.5; S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution (0.55 g / mL) after stirring, adding Tris-HCl buffer to adjust the pH value to 9 after stirring again, heating for reaction (40°C, 10 h), centrifuging, washing and drying to obtain modified montmorillonite; wherein the amount ratio of pre-modified montmorillonite, deionized water and dopamine aqueous solution is 1 g:45 mL:1 g; S5. Compounding: According to the usage ratio of modified chitosan, modified montmorillonite and deionized water being 2 g:0.6 g:10 mL, the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 are added into deionized water respectively, heated and stirred (35°C, 3.5 h), and then filtered, dried and sieved through 100 mesh to obtain functional particles.
[0034] In this embodiment, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0035] Example 3
[0036] A high barrier composite packaging material, which consists of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin was added to deionized water in a mass ratio of 65:12:5.5, and then functional particles were added after stirring (the amount added was half of the mass of all functional particles). After heating and stirring (55°C, 3h), solution I was obtained and set aside. (2) According to the mass ratio of polylactic acid, mixed solution and functional particles being 35:10:5, polylactic acid was added to the mixed solution (prepared by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4), and then the functional particles were added after stirring (the amount added was half of the mass of all functional particles), and after heating and stirring treatment (50°C, 4.5h), solution II was obtained; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0037] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (70°C, 1h) at a ratio of 1g titanium dioxide to concentrated acid (5.5mL). After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2. Immobilization of titanium dioxide: chitosan was added to deionized water, and then the modified titanium dioxide obtained in step S1 was added, and after being stirred evenly, acetic acid was added to adjust the pH value of the system to 5.5, followed by heating and stirring treatment (35°C, 4h). After the treatment was completed, the modified chitosan was obtained by centrifugation, washing, and drying. The amount ratio of chitosan, deionized water, and modified titanium dioxide was 1g: 10mL: 0.48. S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution (0.58 g / mL) after stirring, adding Tris-HCl buffer to adjust the pH value to 9 after stirring again, heating for reaction (40°C, 10 h), centrifuging, washing and drying to obtain modified montmorillonite; wherein the amount ratio of pre-modified montmorillonite, deionized water and dopamine aqueous solution is 1 g:45 mL:1 g; S5. Compounding: According to the usage ratio of modified chitosan, modified montmorillonite and deionized water being 2 g:0.55 g:10 mL, the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 are added into deionized water respectively, heated and stirred (35°C, 3.5 h), and then filtered, dried and sieved through 100 mesh to obtain functional particles.
[0038] In this embodiment, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0039] Comparative Example 1
[0040] Compared with Example 1, Comparative Example 1 does not use functional particles to treat PVA resin and polylactic acid respectively. Specifically, the comparative example provides a high barrier composite packaging material, which is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: PVA resin, polylactic acid, dimethyl sulfoxide and functional particles are added to deionized water, and heated and stirred (55°C, 3h). The amount of each substance used is the same as in Example 1.
[0041] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (70°C, 1h) at a ratio of 1g titanium dioxide to concentrated acid (5.5mL). After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2. Immobilization of titanium dioxide: chitosan was added to deionized water, and then the modified titanium dioxide obtained in step S1 was added, and after being stirred evenly, acetic acid was added to adjust the pH value of the system to 5.5, followed by heating and stirring treatment (35°C, 3.5h). After the treatment was completed, the modified chitosan was obtained by centrifugation, washing, and drying. The amount ratio of chitosan, deionized water, and modified titanium dioxide was 1g: 10mL: 0.5; S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution (0.55 g / mL) after stirring, adding Tris-HCl buffer to adjust the pH value to 8.8 after stirring again, heating for reaction (40°C, 10 h), centrifuging, washing and drying to obtain modified montmorillonite; wherein the amount ratio of pre-modified montmorillonite, deionized water and dopamine aqueous solution is 1 g:45 mL:0.95 g; S5. Compounding: According to the usage ratio of modified chitosan, modified montmorillonite and deionized water being 2 g:0.65 g:10 mL, the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 are added into deionized water respectively, heated and stirred (35°C, 3.5 h), and then filtered, dried and sieved through 100 mesh to obtain functional particles.
[0042] In this comparative example, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0043] Comparative Example 2
[0044] Compared with Example 1, S2 is omitted in the preparation process of the functional particles in Comparative Example 2. Specifically, in Comparative Example 2, a high barrier composite packaging material is provided, which is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin was added to deionized water in a mass ratio of 65:13:6, and then functional particles were added after stirring (the amount added was half of the mass of all functional particles). After heating and stirring (55°C, 3h), solution I was obtained and set aside. (2) According to the mass ratio of polylactic acid, mixed solution and functional particles being 35:9:6, polylactic acid was added to the mixed solution (prepared by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4), and then the functional particles were added after stirring (the amount added was half of the mass of all functional particles), and after heating and stirring (55°C, 3h), solution II was obtained; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0045] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (70°C, 1h) at a ratio of 1g titanium dioxide to concentrated acid (5.5mL). After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2, take chitosan and set aside; S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution (0.55 g / mL) after stirring, adding Tris-HCl buffer to adjust the pH value to 8.8 after stirring again, heating for reaction (40°C, 10 h), centrifuging, washing and drying to obtain modified montmorillonite; wherein the amount ratio of pre-modified montmorillonite, deionized water and dopamine aqueous solution is 1 g:45 mL:0.95 g; S5. Compounding: The modified titanium dioxide obtained in step S1, the chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 are added to deionized water respectively, heated and stirred (35° C., 3.5 h), and then filtered, dried and sieved through 100 mesh to obtain functional particles; the amount of each substance used is the same as in Example 1.
[0046] In this comparative example, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2 Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0047] Comparative Example 3
[0048] Compared with Example 1, in the preparation process of the functional particles in Comparative Example 3, step S4 is omitted. Specifically, in Comparative Example 3, a high barrier composite packaging material is composed of an aluminum foil layer, a vinyl resin heat-sealing coating, a composite coating, a VC glue coating, a polyurethane heat-sealing coating and a polyvinyl chloride sheet from top to bottom; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin was added to deionized water in a mass ratio of 65:13:6, and then functional particles were added after stirring (the amount added was half of the mass of all functional particles). After heating and stirring (55°C, 3h), solution I was obtained and set aside. (2) According to the mass ratio of polylactic acid, mixed solution and functional particles being 35:9:6, polylactic acid was added to the mixed solution (prepared by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4), and then the functional particles were added after stirring (the amount added was half of the mass of all functional particles), and after heating and stirring (55°C, 3h), solution II was obtained; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
[0049] The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: titanium dioxide is placed in 98% concentrated sulfuric acid for treatment (70°C, 1h) at a ratio of 1g titanium dioxide to concentrated acid (5.5mL). After the treatment, the titanium dioxide is filtered, washed and dried to obtain modified titanium dioxide. S2. Immobilization of titanium dioxide: chitosan was added to deionized water, and then the modified titanium dioxide obtained in step S1 was added, and after being stirred evenly, acetic acid was added to adjust the pH value of the system to 5.5, followed by heating and stirring treatment (35°C, 3.5h). After the treatment was completed, the modified chitosan was obtained by centrifugation, washing, and drying. The amount ratio of chitosan, deionized water, and modified titanium dioxide was 1g: 10mL: 0.5; S3. Pre-modification of montmorillonite: montmorillonite was added to deionized water, and CTAB was added under heating and stirring conditions, and then the heating and stirring temperature was maintained for reaction (75°C, 4h). After the reaction was completed, the pre-modified montmorillonite was obtained by filtration and drying; wherein the dosage ratio of montmorillonite, deionized water, and CTAB was 1g:10mL:0.5g; S4. Compounding: According to the usage ratio of modified chitosan, pre-modified montmorillonite and deionized water of 2g:0.65g:10 mL, the modified chitosan obtained in step S2 and the pre-modified montmorillonite obtained in step S3 are added into deionized water respectively, heated and stirred (35°C, 3.5h), and then filtered, dried and sieved through 100 mesh to obtain functional particles.
[0050] In this comparative example, a method for preparing a high barrier composite packaging material is also provided, comprising the following steps: (1) On the surface of the aluminum foil layer, the pressure should be 5.5 g / m 2Applying vinyl resin heat seal adhesive in a coating amount of , and forming a vinyl resin heat seal coating after drying; (2) On the surface of vinyl resin heat seal coating, the 2 Apply the coating liquid in a coating amount of , and form a composite coating after drying; (3) On the composite coating surface, the 2 Apply VC glue at a coating amount of , and form a VC glue coating after drying; (4) On the surface of VC glue coating, 5 g / m 2 Applying the polyurethane heat-sealing adhesive in a coating amount of , and forming a polyurethane heat-sealing coating after drying to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain a high barrier composite packaging material.
[0051] The iodine-blocking packaging materials prepared in Example 1 and Comparative Examples 1 to 4 were tested in the following manner: Iodine barrier performance test: The above-mentioned iodine barrier packaging material is made into an iodine cap, and an iodine-containing molecular drug is placed in it. After standing for 2 months, the iodine content is analyzed using potentiometric analysis.
[0052] Oxygen permeability test: The test is carried out in accordance with GB / T1038.1-2022.
[0053] Water vapor barrier test: The test is carried out in accordance with GB / T1037-2021.
[0054] Tensile strength test: refer to GB / T 1040.3-2006.
[0055] The specific test results are shown in Table 1.
[0056] Table 1 Performance test results
[0057] It can be seen from Table 1 that the iodine-barrier packaging material prepared in the present invention has good iodine-barrier, oxygen-barrier and water vapor-barrier properties, good tensile strength and excellent comprehensive properties.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high barrier composite packaging material, characterized in that: From top to bottom, it is composed of aluminum foil layer, vinyl resin heat-seal coating, composite coating, VC glue coating, polyurethane heat-seal coating and polyvinyl chloride sheet; The composite coating is obtained by coating a coating liquid, and the preparation of the coating liquid comprises the following steps: (1) PVA resin is added to deionized water, and then the first part of functional particles is added after stirring. After heating and stirring, solution I is obtained and set aside; (2) adding polylactic acid to the mixed solution, stirring, and then adding the second part of functional particles, heating and stirring, to obtain solution II; (3) Add the obtained solution I to the obtained solution II and stir until evenly mixed.
2. The high barrier composite packaging material according to claim 1, characterized in that: In step (1), the mass ratio of PVA resin, deionized water, and the first part of functional particles is 60-80:10-15:4-8; the stirring treatment temperature is 50-65°C, and the treatment time is 2-6h; In step (2), the mass ratio of polylactic acid, mixed solution and the second part of functional particles is 20-40:6-12:4-8; the mass ratio of the first part of functional particles and the second part of functional particles is 1:1; the mixed solution is obtained by mixing dimethyl sulfoxide and deionized water in a volume ratio of 1:4; the stirring treatment temperature is 50-65°C, and the treatment time is 2-6h.
3. The high barrier composite packaging material according to claim 2, characterized in that: The preparation of functional particles includes the following steps: S1. Modification of titanium dioxide: treating titanium dioxide in concentrated acid, filtering, washing and drying to obtain modified titanium dioxide; S2. Immobilization of titanium dioxide: chitosan is added to deionized water, and then the modified titanium dioxide obtained in step S1 is added, and after being stirred evenly, acetic acid is added to adjust the pH value of the system, followed by heating and stirring. After the treatment is completed, the modified chitosan is obtained by centrifugation, washing, and drying. S3, pre-modification of montmorillonite: adding montmorillonite to deionized water, adding CTAB under heating and stirring conditions, then maintaining the heating and stirring temperature for reaction, after the reaction is completed, filtering and drying to obtain pre-modified montmorillonite; S4, modification of montmorillonite: adding the pre-modified montmorillonite obtained in step S3 to deionized water, adding dopamine aqueous solution after stirring, adding Tris-HCl buffer to adjust the pH value after stirring again, heating for reaction, centrifuging, washing and drying to obtain modified montmorillonite; S5. Compounding: adding the modified chitosan obtained in step S2 and the modified montmorillonite obtained in step S4 into deionized water respectively, heating and stirring, and then filtering, drying and sieving to obtain functional particles.
4. The high barrier composite packaging material according to claim 3, characterized in that: In step S1, the concentrated acid is 98% concentrated sulfuric acid, the treatment temperature is 70-85° C., and the treatment time is 1-4 h; the dosage ratio of titanium dioxide to concentrated acid is 1 g: 3-6 mL.
5. The high barrier composite packaging material according to claim 3, characterized in that: In step S2, the pH value of the system is 4.5-6.5; the dosage ratio of chitosan, deionized water, and modified titanium dioxide is 1 g: 5-10 mL: 0.45-0.65; The heating and stirring treatment temperature is 30~35℃, and the treatment time is 2~6h.
6. The high barrier composite packaging material according to claim 3, characterized in that: In step S3, the usage ratio of montmorillonite, deionized water and CTAB is 1 g: 5-12 mL: 0.4-0.65 g; The heating and stirring temperature is 70~85℃, and the reaction time is 2~6h.
7. The high barrier composite packaging material according to claim 3, characterized in that: In step S4, the pH value of the system is adjusted to 8-9; the dosage ratio of the pre-modified montmorillonite, deionized water, and dopamine aqueous solution is 1 g: 30-60 mL: 0.8-1.2 g; The concentration of dopamine aqueous solution is 0.45~0.85 g / mL; The heating reaction temperature is 35~45℃ and the reaction time is 6~18h.
8. The high barrier composite packaging material according to claim 3, characterized in that: In step S5, the usage ratio of modified chitosan, modified montmorillonite and deionized water is 2 g: 0.5-0.8 g: 6-12 mL; The heating and stirring temperature is 30~35℃, and the heating and stirring treatment time is 2~6h; The sieving mesh number is 80~150 mesh.
9. A method for preparing the high barrier composite packaging material according to any one of claims 1 to 8, characterized in that: The steps include: (1) coating a vinyl resin heat-sealing adhesive on the surface of the aluminum foil layer and drying the adhesive to form a vinyl resin heat-sealing coating; (2) applying a coating liquid on the surface of the vinyl resin heat seal coating and drying it to form a composite coating; (3) Apply VC glue on the surface of the composite coating and form a VC glue coating after drying; (4) applying polyurethane heat-sealing adhesive on the surface of the VC glue coating, and drying to form a polyurethane heat-sealing coating to obtain a semi-finished product; (5) The semi-finished product obtained in step (4) is compounded with a polyvinyl chloride sheet and cut into pieces to obtain an iodine-blocking packaging material.
10. The preparation method according to claim 9, characterized in that: The coating amount of vinyl resin heat sealant is 5~8g / m 2 ; The coating amount of the coating liquid is 3~5 g / m 2 ; The coating amount of VC glue is 4~6 g / m 2 ; The coating amount of polyurethane heat sealant is 5~8 g / m 2 .
Citation Information
Patent Citations
Iodine-resistant packaging material and production process thereof
CN117183483A
Iodine-resistant aluminum foil blister packaging structure
CN220841724U
Preparation method for polylactic acid composite paper plastic package material
CN105603812A
Gas barrier laminate, coating liquid for producing same, packaging material, packaging body, and packaged article
CN114981375A
Press-through pack wrapping container
JP1999235790A
Cited By
Anti-aging floor glue and preparation method thereof
CN120623926A
Anti-aging floor adhesive and preparation method thereof
CN120623926B
High-barrier coating for paper bubble cap, preparation method of high-barrier coating and paper bubble cap material
CN121519353A